Natural experiment examining the longitudinal association between change in residential segregation and youth cardiovascular health across race/ethnicity and gender in the USA. Issue 7 (10th May 2018) - D'Agostino, Emily M; Patel, Hersila H; Ahmed, Zafar; Hansen, Eric; Mathew, M Sunil; Nardi, Maria I; Messiah, Sarah E
Abstract : Background: Identifying how racial/ethnic residential segregation and mobility may impact health can guide innovative strategies for reducing youth disparities. Methods: This natural experiment examined the association between change in residential segregation and cardiovascular health outcomes across race/ethnicity and gender for youth (n=2250, mean age 9.1 years, 54% male; 51% Hispanic, 49% non-Hispanic black (NHB); 49% high area poverty) attending a multisite park-based afterschool fitness programme in Florida, USA. Two-level generalised linear mixed models with random intercepts for park effects were fit to test the change in segregation–cardiovascular health association over two school years. Results: After covariate adjustment (individual-level gender, race/ethnicity, age, time and park-area poverty), greater improvements in cardiovascular health including body mass index percentile, sum of skinfold thicknesses, systolic/diastolic blood pressure percentiles and 400 m run time were found for youth who attended the program in a less segregated area compared with their home area (p<0.05 for all outcomes). NHB girls showed the greatest cardiovascular health improvements. Specifically, compared with the reference group (no change in segregation), skinfold thicknesses and systolic blood pressure percentiles decreased 17% (incidence rate ratio (IRR) 95% CI 0.81 to 0.86) and 16% (IRR 95% CI 0.82 to 0.87), respectively, versus 1% increase for both outcomes (IRR 95% CI 0.98 to 1.05) and (IRR 95% CI 0.98 to 1.05), respectively, for movement to less versus more segregated areas. Conclusion: In light of a continually expanding youth obesity epidemic, the global effort to reduce health inequities may be supported through Parks and Recreation Departments given potential to expand geographic mobility for low resource subgroups.